Cek Bocek Selesek Reen Sury Traditional Legal Community In Sumbawa (1512 – 2023) - Nurmadiah, Nurmadiah; Gunawan, Jasardi (Yupa: Historical Studies Journal, 2024)
This research aims to determine the history of the Cek Bocek indigenous community in Sumbawa and the fundamental differences between the general community in Sumbawa. This research uses the historical method. In this case, all documents considered important in the Cek Bocek traditional community will be used as one discussion narrated by taking the essence or main points. The existence of the Cek Bocek traditional community in Sumbawa began in 1492, and in 1512, the form of government of the Selesek chiefdom led by Dewa Datu Awan Maskuing began. The fundamental difference between the Cek Bocek Selesek Reen Sury indigenous community and other communities in Sumbawa lies in the language used, called the Berco language. The Cek Bocek indigenous communities have traditional institutions and mechanisms for meeting meetings, which are referred to as Rapulun Adat and are led by one traditional leader as tribal head, and have a jointly protected customary area which is outlined in a participatory map approved by the village government, and has different traditional rituals such as NABAR (Tulak Bala), Pungka Inu (customary forest welfare), zakat alms every post-harvest season, Enang Uran (asking for rain) in Tiu Mareng. Also, customary law rules and property are left behind to maintain ancestral traditions